exo-endo isomerism of carboranes: unusual geometries of C2B5X7 (X=Cl, Br) and C2B7Cl9 with exo-skeletal BCl2 groups on carbon revealed by joint spectroscopic/computational studies - Keller, Willi; Conrad, Jürgen; Hofmann, Matthias (ChemistrySelect, 2023)
Reexamination of the co-pyrolysis reactions of B2Cl4 with C2Cl4 at 350 °C and of B2Br4 with CBr4 at 300 °C in vacuo confirmed the carboranes C2B5Cl7 (1), C2B7Cl9 (2), and C2B5Br7 (3) as low-yield products. While 1 only could be concentrated by repeated vacuum fractionation, 2 and 3 could now be isolated from the conglomerate mixtures for a full spectroscopic characterization and the compounds were verified in their geometries by detailed DFT computations. Surprisingly, the perhalogenated carboranes do not adopt the expected “all-endo”-geometries with cluster sizes derived by the sum of the n boron and two carbon atoms (n+2) as known from the syntheses of the parent closo-carboranes C2BnHn+2. Instead, DFT/GIAO(ZORA)/NMR (GIAO for X=Cl, ZORA for X=Br) computations revealed that the perhalogenated carboranes favor structures with BX2 groups as exo-skeletal ligands attached to both cage-carbon atoms yielding the five-vertex closo-1,5-(CBX2)2B3X3 (1: X=Cl; 3: X=Br) and the seven-vertex closo-2,4-(CBCl2)2B5Cl5 for 2. In contrast to these perhalogenated carboranes, analogous computations on the hydrogen substituted carboranes C2BnHn+2, silaboranes Si2BnHn+2 and Si2BnXn+2 (n=5, 7) show in all cases a thermodynamic favorization of structures where all boron atoms of the formula are endo-skeletally incorporated into the cluster frameworks.